A prescript for monetary theory - Wallace, Neil (1996)
The article propases a dictum or rule for the methodology of monetary theory modeling. The dictum or rule is that money should not be a primitive concept in monetary theory, but its existence and its value should result from some general equilibrium situation. The article distinguishes, among current monetary models, which ones satisfy the dictum and which ones don't. As an example, it also presents a "pairwise meetings" model that satisfies it.